A method for preparing water-resistant and anti-aging water-based coating

By synthesizing alkenyl organic fluorosilicone polymers and modified nano titanium dioxide with acrylic acid and methyl methacrylate, the method addresses poor water resistance and aging issues in water-based acrylic coatings, resulting in a coating with improved hydrophobicity and UV resistance.

CN118146690BActive Publication Date: 2024-12-13COSCO KANSAI PAINT SHANGHAI CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202410261773.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-07
Publication Date
2024-12-13
Estimated Expiration
2044-03-07

AI Technical Summary

Technical Problem

Existing water-based acrylic coatings suffer from poor water resistance and rapid aging due to ultraviolet radiation, leading to issues such as coating degradation, loss of gloss, and reduced mechanical properties.

Method used

A method involving the synthesis of alkenyl organic fluorosilicone polymers and modified nano titanium dioxide with acrylic acid and methyl methacrylate, followed by polymerization and blending with talc powder to create a water-resistant and anti-aging acrylic resin, which is then formulated into a water-based coating.

Benefits of technology

The resulting coating exhibits enhanced water resistance and anti-aging properties, with reduced water absorption and maintained tensile strength even after exposure to ultraviolet radiation, thanks to the high cross-linking density and UV shielding effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004731132060000031
    Figure BDA0004731132060000031
  • Figure BDA0004731132060000111
    Figure BDA0004731132060000111
  • Figure BDA0004731132060000121
    Figure BDA0004731132060000121
Patent Text Reader

Abstract

The invention relates to the technical field of water-based coatings, and discloses a method for preparing a water-resistant and anti-aging water-based coating. The C-F bond energy in an organic fluorine silicon polymer is high. Compared with hydrogen atoms, fluorine atoms are more easily embedded in the polymer, thereby blocking the channel for water molecules to migrate into the interior of a coating film. The terminal hydroxypropyl polysiloxane can form a hydrophobic layer on the surface of the coating film, while the alkenyl organic fluorine silicon polymer and the alkenyl in a modified nano titanium dioxide structure can polymerize with acrylic monomers, thereby increasing the crosslinking density and forming a dense surface layer. After film formation, the organic fluorine and organic silicon in the polymer are arranged outwardly in a directional manner, thereby reducing the surface energy of the coating film, thereby making the coating film have excellent water resistance. The nano titanium dioxide particles have a small size effect and a quantum size effect, and have a strong absorption effect on ultraviolet rays. The modified nano titanium dioxide has good compatibility with the coating, thereby improving the anti-aging performance of the water-based coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-based coatings, in particular to a method for preparing water-resistant and anti-aging water-based coatings. Background Art

[0002] Paint plays a very important role in production and life. The use of paint can prevent the surface of objects from being affected by climate corrosion, chemical corrosion and sunlight, prevent or reduce the direct friction and impact on the surface of objects, and can decorate, protect and mark objects. Although most of the paints on the market are simple to make and cheap, they have relatively simple functions. In some special working environments, simple paints cannot meet people's needs. At present, various environmentally friendly paints are emerging in an endless stream. Acrylic paints have the advantages of good film-forming properties, non-toxicity and non-volatile, numerous synthetic monomers and low prices. They have been widely used in various fields, but their water resistance is poor, and their performance in weather resistance and other aspects is also unsatisfactory. Therefore, the development of a water-resistant and anti-aging water-based paint has become a hot topic of current research.

[0003] Acrylic resin coatings are usually prone to poor adhesion during use, causing the coating to fall off, especially in the rainy season in the south, when the air is humid, the coating has poor water resistance, and the coating falls off seriously; at the same time, due to the effects of ultraviolet rays, heat, oxygen, water and other factors, the coating film will be oxidized and damaged, causing loss of gloss, powdering, cracking and other phenomena, thereby causing the decline of its various properties and then losing its use value; Chinese patent CN114456651B discloses a water-based acrylic waterproof coating and a preparation method thereof, wherein the water-based acrylic resin is used as the main film-forming substance, and is compounded with emulsified asphalt, fillers and other functional additives to obtain a water-based acrylic waterproof coating with good The present invention has good acid and alkali resistance, salt water resistance, water resistance and mechanical properties, but it is a pure acrylic resin coating, and has the disadvantages of poor anti-aging performance; most of the existing technologies use light stabilizer additives such as benzophenone series, benzotriazole series, salicylate series, etc., but these organic substances have certain toxicity, and their ultraviolet shielding performance will gradually decrease with the extension of the sun exposure time of the coating; there are also technologies that add light shielding agents such as nano titanium dioxide, nano zinc oxide, etc. to acrylic coatings, which can effectively reduce the light aging of polymers and improve their resistance to ultraviolet aging, but the dispersibility of nano materials in coatings is poor, which hinders the performance of their special functions and makes the stability of the coating worse.

[0004] Organic silicon fluorine elements can improve the water resistance, oil resistance and wear resistance of acrylic resin coatings, but it is difficult to resist damage caused by light radiation, and ultraviolet rays are an important factor that accelerates the aging of acrylic resin coatings. The present invention synthesizes alkenyl organic fluorine silicon polymers and polymerizes them with acrylic acid, methyl methacrylate, modified nano titanium dioxide, etc. to prepare a water-based acrylic coating with both water resistance and anti-aging properties. The coating is green and environmentally friendly and has a simple process. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a water-resistant and anti-aging water-based coating, thereby solving the problem that the existing water-resistant coating has poor water resistance and is easy to age.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a water-resistant and anti-aging water-based coating comprises the following steps:

[0008] (1) sodium dodecyl sulfate and deionized water are added to a reaction flask equipped with a reflux condenser and a dropping funnel, stirred to dissolve, methyl methacrylate, butyl acrylate, acrylic acid, alkenyl organic fluorosilicone polymer and modified titanium dioxide are added, stirred evenly at 55-65° C., an aqueous solution of ammonium persulfate is added dropwise, and then reacted at 75-80° C. for 3-5 hours, cooled to 35-45° C., and ammonia water is added to adjust the pH to obtain a water-resistant and anti-aging acrylic resin.

[0009] (2) Add water-resistant and anti-aging acrylic resin and talcum powder into a reaction flask, mix them evenly, add dispersant, leveling agent and defoaming agent, and disperse them evenly with a high-speed disperser to obtain a water-resistant and anti-aging water-based coating.

[0010] Furthermore, in step (1), the ratio of methyl methacrylate, butyl acrylate, acrylic acid, alkenyl organic fluorosilicone polymer, and modified titanium dioxide is (20-35) g:100 g:(5-10) g:(2-15) g:(1-10) g.

[0011] Furthermore, the mass fraction of the ammonium persulfate aqueous solution in step (1) is 5-10 wt %.

[0012] Furthermore, in step (1), the pH of the solution is adjusted to 7-8 by using aqueous ammonia.

[0013] Furthermore, the method for preparing the alkenyl organofluorosilicone polymer in step (1) comprises the following steps:

[0014] Step S1: In a nitrogen atmosphere, add 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide) and xylene to a reaction flask equipped with a reflux condenser, stir evenly, add methacrylic acid and triethylamine, stir to react, and after the reaction is completed, perform vacuum distillation to obtain dodecafluorooctane-1,8-diylbis(methacrylate). The preparation reaction formula is as follows:

[0015]

[0016] Step S2, under a nitrogen atmosphere, add dodecafluorooctane-1,8-diylbis(methacrylate), terminal hydroxypropyl polysiloxane, isophorone diisocyanate and deionized water to a reaction flask equipped with a thermometer and a reflux condenser, stir evenly, add dibutyltin dilaurate, stir to react, and after the reaction is completed, concentrate under reduced pressure to obtain an olefinic organofluorosilicone polymer.

[0017] Furthermore, in step S1, the ratio of 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide), methacrylic acid and triethylamine is 1 mol:(5-10) mol:(2.1-2.3) mol.

[0018] Furthermore, in step S1, the reaction temperature is 95-110° C., and the reaction time is 2-5 h.

[0019] Furthermore, in step S2, the ratio of dodecafluorooctane-1,8-diylbis(methacrylate), terminal hydroxypropyl polysiloxane, isophorone diisocyanate, and dibutyltin dilaurate is 1 mol:(1-1.05) mol:(2-2.2) mol:(0.01-0.03) mol.

[0020] Furthermore, in step S2, the reaction temperature is 85-95° C., and the reaction time is 3-8 h.

[0021] By adopting the above technical solution, the beneficial effects of the present invention are:

[0022] The invention firstly utilizes the epoxy group of 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide) to undergo a ring-opening reaction with the carboxyl group of methacrylic acid to obtain dodecafluorooctane-1,8-diylbis(methacrylate), and then polymerizes with terminal hydroxypropyl polysiloxane and isophorone diisocyanate to obtain an alkenyl organic fluorosilicone polymer, and then the alkenyl organic fluorosilicone polymer, modified titanium dioxide and methacrylic acid monomers are reacted under the action of an initiator, ammonium persulfate, to obtain a water-resistant and anti-aging acrylic resin, and finally the resin is uniformly blended with talc powder, an auxiliary agent and the like to obtain a water-resistant and anti-aging water-based coating.

[0023] The CF bond energy in the organic fluorine silicon polymer prepared by the present invention is high. Compared with hydrogen atoms, fluorine atoms are more easily embedded in the polymer, blocking the channel for water molecules to migrate into the coating film; the terminal hydroxypropyl polysiloxane itself is hydrophobic and can form a hydrophobic layer on the surface of the coating film. At the same time, the alkenyl organic fluorine silicon polymer and the alkenyl in the modified nano titanium dioxide structure can be polymerized with acrylic monomers, increasing the crosslinking density, thereby enhancing the contraction force of the generated polymer network, and further forming a dense surface layer, inhibiting water from penetrating into the coating film, thereby reducing the water absorption rate of the coating film. After film formation, the organic fluorine and organic silicon in the polymer are arranged outwardly in a directional manner, thereby reducing the surface energy of the coating film, so that the product has excellent hydrophobic performance; the organic fluorine silicon monomer has a low surface energy, can migrate to the surface during the film formation process, is more easily enriched on the surface of the coating film, makes the surface of the coating film denser, increases water resistance, and is conducive to improving the contact angle.

[0024] Nano titanium dioxide particles have small size effect and quantum size effect, and have a strong absorption effect on ultraviolet rays. They can absorb ultraviolet rays in the medium and long wave regions. The absorption and scattering of ultraviolet rays constitute a shielding effect on ultraviolet rays. The modified nano titanium dioxide has good compatibility with acrylic resin coatings. After the olefin groups on its surface participate in the polymerization, the dispersibility with the coating is improved, thereby increasing the tensile strength of the coating, reducing the damage of ultraviolet rays to acrylic molecules, and improving the anti-aging properties of acrylic resin. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The terminal hydroxypropyl polysiloxane was prepared with reference to the journal "Synthesis and Performance Research of Silicone Rubber" (Volume 39, Issue 1, 2011): 50g of octamethylcyclotetrasiloxane and 0.05% of tetramethylammonium hydroxide siliconate catalyst were added to a 100mL three-necked flask, and dehydrated under reduced pressure at 40°C / 10mmHg for 1h, then heated to 80°C under nitrogen protection, and after the tetramethylammonium hydroxide siliconate was dissolved, 0.6g of 1,3-dihydroxypropyl-1,1,3,3-tetramethyldisiloxane was added, and the temperature was raised to 95°C, and balanced copolymerization was performed for more than 12h, and then the tetramethylammonium hydroxide siliconate was decomposed at 150°C for 1h, and low-boiling products were removed under reduced pressure to obtain the terminal hydroxypropyl polysiloxane.

[0027] Preparation of modified nano-titanium dioxide: Add 1 g of nano-titanium dioxide, 0.05 g of KH570, 10 mL of deionized water and 20 mL of ethanol into a reaction flask, adjust the pH to 7 with 25% ammonia water, ultrasonically disperse at 50°C and 60 Hz for 100 min, filter, wash with deionized water, and dry to obtain modified nano-titanium dioxide.

[0028] 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide), CAS number 74328-56-6.

[0029] Methacrylic acid, CAS number is 79-41-4.

[0030] Example 1

[0031] (1) Under nitrogen atmosphere, 25 mmol of 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide) and 150 mL of xylene were added to a reaction flask equipped with a reflux condenser. After stirring evenly, 200 mmol of methacrylic acid and 55 mmol of triethylamine were added, and the mixture was reacted at 105° C. for 3 h. The mixture was distilled under reduced pressure to obtain dodecafluorooctane-1,8-diyl bis(methacrylate).

[0032] (2) Under a nitrogen atmosphere, 15 mmol of dodecafluorooctane-1,8-diylbis(methacrylate), 15.3 mmol of terminal hydroxypropyl polysiloxane, 32.2 mmol of isophorone diisocyanate and 210 mL of deionized water were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 0.3 mmol of dibutyltin dilaurate was added, and the mixture was reacted at 90° C. for 7 h. The mixture was concentrated under reduced pressure to obtain an alkenyl organofluorosilicone polymer.

[0033] (3) Add 4 g of sodium dodecyl sulfate and 220 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 25 g of methyl methacrylate, 100 g of butyl acrylate, 8 g of acrylic acid, 2 g of alkenyl organic fluorosilicone polymer and 1 g of modified titanium dioxide, stir evenly at 60° C., add dropwise an 8 wt % aqueous solution of ammonium persulfate, then react at 75° C. for 5 h, cool to 40° C., add aqueous ammonia to adjust the pH to 7, and obtain a water-resistant and anti-aging acrylic resin.

[0034] (4) Add 100 g of water-resistant and anti-aging acrylic resin and 15 g of talcum powder to a reaction flask and mix well, then add 1.5 g of dispersant BYK-9076, 1.3 g of leveling agent BYK-388, and 0.9 g of defoaming agent DF681F, and disperse evenly with a high-speed disperser to obtain a water-resistant and anti-aging water-based coating.

[0035] Example 2

[0036] (1) Under nitrogen atmosphere, 15 mmol of 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide) and 75 mL of xylene were added to a reaction flask equipped with a reflux condenser. After stirring, 75 mmol of methacrylic acid and 31.5 mmol of triethylamine were added, and the mixture was reacted at 110° C. for 2 h. The mixture was distilled under reduced pressure to obtain dodecafluorooctane-1,8-diyl bis(methacrylate).

[0037] (2) Under a nitrogen atmosphere, 8 mmol of dodecafluorooctane-1,8-diylbis(methacrylate), 8 mmol of terminal hydroxypropyl polysiloxane, 16 mmol of isophorone diisocyanate and 80 mL of deionized water were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 0.08 mmol of dibutyltin dilaurate was added, and the mixture was reacted at 95° C. for 3 h. The mixture was concentrated under reduced pressure to obtain an alkenyl organofluorosilicone polymer.

[0038] (3) Add 3 g of sodium dodecyl sulfate and 200 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 30 g of methyl methacrylate, 100 g of butyl acrylate, 10 g of acrylic acid, 5.25 g of alkenyl organic fluorosilicone polymer and 3.25 g of modified titanium dioxide, stir evenly at 65° C., add dropwise a 10 wt % aqueous solution of ammonium persulfate, then react at 80° C. for 3 h, cool to 45° C., add aqueous ammonia to adjust the pH to 8, and obtain a water-resistant and anti-aging acrylic resin.

[0039] (4) Add 100 g of water-resistant and anti-aging acrylic resin and 16 g of talcum powder to a reaction flask and mix well, then add 1.5 g of dispersant BYK-9076, 1.3 g of leveling agent BYK-388, and 0.9 g of defoaming agent DF681F, and disperse evenly with a high-speed disperser to obtain a water-resistant and anti-aging water-based coating.

[0040] Example 3

[0041] (1) Under a nitrogen atmosphere, 30 mmol of 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide) and 240 mL of xylene were added to a reaction flask equipped with a reflux condenser. After stirring, 300 mmol of methacrylic acid and 69 mmol of triethylamine were added, and the mixture was reacted at 95° C. for 5 h. The mixture was distilled under reduced pressure to obtain dodecafluorooctane-1,8-diyl bis(methacrylate).

[0042] (2) Under a nitrogen atmosphere, 20 mmol of dodecafluorooctane-1,8-diylbis(methacrylate), 21 mmol of terminal hydroxypropyl polysiloxane, 44 mmol of isophorone diisocyanate and 300 mL of deionized water were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 0.6 mmol of dibutyltin dilaurate was added, and the mixture was reacted at 85° C. for 8 h. The mixture was concentrated under reduced pressure to obtain an alkenyl organofluorosilicone polymer.

[0043] (3) Add 5 g of sodium dodecyl sulfate and 250 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 25 g of methyl methacrylate, 100 g of butyl acrylate, 7 g of acrylic acid, 8.5 g of alkenyl organic fluorosilicone polymer and 6.5 g of modified titanium dioxide, stir evenly at 55° C., add dropwise a 5 wt % aqueous solution of ammonium persulfate, then react at 75° C. for 5 h, cool to 45° C., add aqueous ammonia to adjust the pH to 8, and obtain a water-resistant and anti-aging acrylic resin.

[0044] (4) Add 100 g of water-resistant and anti-aging acrylic resin and 15 g of talcum powder to a reaction flask and mix well, then add 1.5 g of dispersant BYK-9076, 1.3 g of leveling agent BYK-388, and 0.9 g of defoaming agent DF681F, and disperse evenly with a high-speed disperser to obtain a water-resistant and anti-aging water-based coating.

[0045] Example 4

[0046] (1) Under a nitrogen atmosphere, 5 mmol of 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide) and 30 mL of xylene were added to a reaction flask equipped with a reflux condenser. After stirring, 45 mmol of methacrylic acid and 11.1 mmol of triethylamine were added, and the mixture was reacted at 100° C. for 4 h. The mixture was distilled under reduced pressure to obtain dodecafluorooctane-1,8-diyl bis(methacrylate).

[0047] (2) Under a nitrogen atmosphere, 3 mmol of dodecafluorooctane-1,8-diylbis(methacrylate), 3.12 mmol of terminal hydroxypropyl polysiloxane, 6.15 mmol of isophorone diisocyanate and 42 mL of deionized water were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 0.075 mmol of dibutyltin dilaurate was added, and the mixture was reacted at 90° C. for 6 h. The mixture was concentrated under reduced pressure to obtain an alkenyl organofluorosilicone polymer.

[0048] (3) Add 4 g of sodium dodecyl sulfate and 235 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 20 g of methyl methacrylate, 100 g of butyl acrylate, 10 g of acrylic acid, 11.75 g of alkenyl organic fluorosilicone polymer and 7.75 g of modified titanium dioxide, stir evenly at 65° C., add dropwise a 7 wt % aqueous solution of ammonium persulfate, then react at 80° C. for 5 h, cool to 40° C., add aqueous ammonia to adjust the pH to 7, and obtain a water-resistant and anti-aging acrylic resin.

[0049] (4) Add 100 g of water-resistant and anti-aging acrylic resin and 20 g of talcum powder to a reaction flask and mix well, then add 1.5 g of dispersant BYK-9076, 1.3 g of leveling agent BYK-388, and 0.9 g of defoaming agent DF681F, and disperse evenly with a high-speed disperser to obtain a water-resistant and anti-aging water-based coating.

[0050] Example 5

[0051] (1) Under a nitrogen atmosphere, 12 mmol of 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide) and 80 mL of xylene were added to a reaction flask equipped with a reflux condenser. After stirring, 95 mmol of methacrylic acid and 24.6 mmol of triethylamine were added, and the mixture was reacted at 105° C. for 4 h. The mixture was distilled under reduced pressure to obtain dodecafluorooctane-1,8-diyl bis(methacrylate).

[0052] (2) Under a nitrogen atmosphere, 5 mmol of dodecafluorooctane-1,8-diylbis(methacrylate), 5.2 mmol of terminal hydroxypropyl polysiloxane, 10.7 mmol of isophorone diisocyanate and 70 mL of deionized water were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 0.012 mmol of dibutyltin dilaurate was added, and the mixture was reacted at 90° C. for 8 h. The mixture was concentrated under reduced pressure to obtain an alkenyl organofluorosilicone polymer.

[0053] (3) Add 5 g of sodium dodecyl sulfate and 245 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 20 g of methyl methacrylate, 100 g of butyl acrylate, 5 g of acrylic acid, 15 g of alkenyl organic fluorosilicone polymer and 10 g of modified titanium dioxide, stir evenly at 65° C., add dropwise a 10 wt % aqueous solution of ammonium persulfate, then react at 75° C. for 3 h, cool to 45° C., add aqueous ammonia to adjust the pH to 8, and obtain a water-resistant and anti-aging acrylic resin.

[0054] (4) Add 100 g of water-resistant and anti-aging acrylic resin and 18 g of talcum powder to a reaction flask and mix well, then add 1.5 g of dispersant BYK-9076, 1.3 g of leveling agent BYK-388, and 0.9 g of defoaming agent DF681F, and disperse evenly with a high-speed disperser to obtain a water-resistant and anti-aging water-based coating.

[0055] Comparative Example 1

[0056] (1) To a reaction flask equipped with a reflux condenser and a dropping funnel, 4 g of sodium dodecyl sulfate and 220 mL of deionized water were added and stirred to dissolve. 25 g of methyl methacrylate, 100 g of butyl acrylate, 8 g of acrylic acid and 2 g of alkenyl organofluorosilicone polymer (prepared according to the method of Example 1) were added and stirred uniformly at 60° C. An aqueous solution of ammonium persulfate with a mass fraction of 8 wt % was added dropwise, followed by reaction at 75° C. for 5 h, cooling to 40° C., and adding aqueous ammonia to adjust the pH to 7 to obtain an acrylic resin.

[0057] (2) Add 100 g of acrylic resin and 15 g of talcum powder to a reaction flask and mix well. Then add 1.5 g of dispersant BYK-9076, 1.3 g of leveling agent BYK-388, and 0.9 g of defoaming agent DF681F. After being dispersed evenly by a high-speed disperser, a water-based coating is obtained.

[0058] Comparative Example 2

[0059] (1) Add 4 g of sodium dodecyl sulfate and 220 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 25 g of methyl methacrylate, 100 g of butyl acrylate, 8 g of acrylic acid and 1 g of modified titanium dioxide, stir evenly at 60° C., dropwise add an 8 wt % ammonium persulfate aqueous solution, then react at 75° C. for 5 h, cool to 40° C., add aqueous ammonia to adjust the pH to 7, and obtain an acrylic resin.

[0060] (2) Add 100 g of acrylic resin and 15 g of talcum powder to a reaction flask and mix well. Then add 1.5 g of dispersant BYK-9076, 1.3 g of leveling agent BYK-388, and 0.9 g of defoaming agent DF681F. After being dispersed evenly by a high-speed disperser, a water-based coating is obtained.

[0061] Comparative Example 3

[0062] (1) Add 4 g of sodium dodecyl sulfate and 220 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 25 g of methyl methacrylate, 100 g of butyl acrylate and 8 g of acrylic acid, stir evenly at 60° C., dropwise add an 8 wt % aqueous solution of ammonium persulfate, then react at 75° C. for 5 h, cool to 40° C., add aqueous ammonia to adjust the pH to 7, and obtain an acrylic resin.

[0063] (2) Add 100 g of acrylic resin and 15 g of talcum powder to a reaction flask and mix well. Then add 1.5 g of dispersant BYK-9076, 1.3 g of leveling agent BYK-388, and 0.9 g of defoaming agent DF681F. After being dispersed evenly by a high-speed disperser, a water-based coating is obtained.

[0064] Preparation of coating film: Take 2 mL of acrylic resin paint and drop it into a surface dish. Let it form a film naturally at room temperature for 5 hours, and then dry it at 80℃ for 6 hours to form a film.

[0065] Water absorption test: Cut the film into small pieces of 10mm×10mm, with an initial mass of G 0 , soak it in water at room temperature for 48 hours, take it out, use filter paper to absorb the water on the surface, and weigh its mass as G 1 The water absorption rate of the membrane is calculated as follows: Water absorption rate = (G 1 -G 0 ) / G 0 ×100%.

[0066] Surface contact angle test: Use a contact angle meter to test, drop 5μL of water on the surface of the film, measure the contact angle of the coating to water, select 5 different points for each sample for measurement, and take the average value as the contact angle of the coating surface.

[0067] Water absorption (%) Contact angle (°) Example 1 9.9 100.6 Example 2 7.6 109.3 Example 3 5.3 118.8 Example 4 4.0 129.4 Example 5 3.4 135.1 Comparative Example 1 10.1 99.8 Comparative Example 2 17.5 79.2 Comparative Example 3 18.3 77.6

[0068] It can be seen from the test results in the above table that with the increase in the amount of alkenyl organic fluorosilicone polymer, the water absorption rate of the water-based coating gradually decreases, and the water absorption rate in Example 5 is only 3.4%. This is because the fluorine atoms in the organic fluorosilicone polymer have large electronegativity, small diameter and high CF bond energy. Compared with hydrogen atoms, fluorine atoms are more easily embedded in the polymer, blocking the channels for water molecules to migrate to the inside of the coating. At the same time, the terminal hydroxypropyl polysiloxane itself is hydrophobic. After addition, the proportion of hydrophobic components in the coating will increase, and a hydrophobic layer will be formed on the surface of the coating. In addition, the alkenyl organic fluorosilicone polymer and the alkenyl in the modified nano titanium dioxide structure can be polymerized with acrylic monomers, which increases the crosslinking density, thereby enhancing the contraction force of the generated polymer network, thereby forming a dense surface layer, inhibiting water from penetrating into the coating, and reducing the water absorption rate of the coating. After film formation, the polymer organic fluorine and silicone are oriented outward, which reduces the surface energy of the coating, so that the product has excellent hydrophobic properties.

[0069] The contact angle of the coating, that is, the surface wetting performance, is determined by the properties and stacking conditions of the atoms or exposed atomic groups on the solid surface. The surface energy of the fluorine monomer is low and it will migrate to the surface during the film formation process. At the same time, the Si-O bond of the terminal hydroxypropyl polysiloxane has the characteristics of large bond energy, low surface energy and small surface tension. Therefore, with the increase in the amount of alkenyl organic fluorosilicone polymer, the low surface energy polysiloxane and fluorine-containing groups are more easily enriched on the surface of the coating, making the surface of the coating denser, increasing the contact angle, and is conducive to improving the hydrophobicity.

[0070] Comparative Example 3 is a pure acrylic resin coating, which has a high water absorption rate, a large contact angle, and poor water resistance; Comparative Example 2 does not contain an olefinic organic fluorosilicone polymer, has a water absorption rate of 17.5%, a contact angle of 79.2°, and poor water resistance.

[0071] Water immersion aging performance test: The prepared coating film was cut into 100mm×50mm specimens, immersed in water for 168h, taken out and wiped dry with a dry cloth, placed in an 80℃ electric blast drying oven for 12h, cooled to room temperature, and subjected to a tensile performance test using a universal tensile testing machine at a tensile speed of 2mm / min.

[0072]

[0073]

[0074] From the test results in the above table, it can be seen that with the increase in the amount of olefinic organic fluorosilicone polymer and modified titanium dioxide, the water resistance of the water-based coating is improved. At the same time, after 168 hours of immersion and heating treatment, the tensile strength of the coating is basically unchanged. This is because, on the one hand, the cross-linked network structure formed inside the coating increases the cross-linking density of the coating, inhibits the penetration of water into the coating, and enhances the water resistance of the coating, which is manifested as an increase in the tensile strength of the coating; on the other hand, because the nano-titanium dioxide particles have a small size effect and a quantum size effect, the modified nano-titanium dioxide has good compatibility with acrylic resin coatings, and the olefinic groups on its surface participate in the polymerization, which improves the dispersibility, thereby improving the tensile properties of the coating.

[0075] UV aging performance test: The prepared coating film was cut into 100mm×50mm samples, placed under a 30W UV lamp, 5cm away from the light source, and irradiated for 240h to test the aging degree of the sample; a universal tensile testing machine was used for tensile performance test, and the tensile speed was 2mm / min.

[0076]

[0077] It can be seen from the test results in the above table that after 30W ultraviolet treatment, the tensile strength of the coating remains basically unchanged, indicating that the prepared coating has excellent anti-aging properties. This is because the added nano-titanium dioxide particles have a small size effect and a quantum size effect, and have a strong absorption effect on ultraviolet rays, so that the coating still has good tensile strength after 240 hours of ultraviolet aging, and can meet the use under a variety of external conditions, broadening the application range of water-based coatings; in Comparative Example 1, no nano-titanium dioxide is added and has no anti-ultraviolet ability, and the tensile strength of the coating decreases significantly after ultraviolet aging.

[0078] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a water-resistant and anti-aging water-based coating, characterized in that: The preparation method comprises the following steps: (1) sodium dodecyl sulfate and deionized water are added to a reaction flask equipped with a reflux condenser and a dropping funnel, stirred to dissolve, methyl methacrylate, butyl acrylate, acrylic acid, alkenyl organic fluorine silicon polymer and modified titanium dioxide are added, stirred evenly at 55-65° C., an aqueous solution of ammonium persulfate is added dropwise, and then reacted at 75-80° C. for 3-5 hours, cooled to 35-45° C., and ammonia water is added to adjust the pH to obtain a water-resistant and anti-aging acrylic resin; (2) Add water-resistant and anti-aging acrylic resin and talcum powder into a reaction flask, mix them evenly, then add dispersant, leveling agent and defoaming agent, and disperse them evenly with a high-speed disperser to obtain a water-resistant and anti-aging water-based coating; The method for preparing the alkenyl organic fluorosilicone polymer in step (1) comprises the following steps: Step S1, under a nitrogen atmosphere, add 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide) and xylene to a reaction flask equipped with a reflux condenser, stir evenly, add methacrylic acid and triethylamine, stir to react, and after the reaction is completed, perform reduced pressure distillation to obtain dodecafluorooctane-1,8-diyl bis(methacrylate); Step S2, under a nitrogen atmosphere, adding dodecafluorooctane-1,8-diylbis(methacrylate), terminal hydroxypropyl polysiloxane, isophorone diisocyanate and deionized water to a reaction flask equipped with a thermometer and a reflux condenser, stirring evenly, adding dibutyltin dilaurate, stirring to react, and after the reaction is completed, concentrating under reduced pressure to obtain an alkenyl organofluorosilicone polymer; The preparation method of the modified titanium dioxide in step (1) comprises the following steps: adding 1 g of nano titanium dioxide, 0.05 g of KH570, 10 mL of deionized water and 20 mL of ethanol into a reaction flask, adjusting the pH to 7 with 25% ammonia water, ultrasonically dispersing at a temperature of 50° C. and a power of 60 Hz for 100 min, filtering, washing with deionized water, and drying to obtain the modified titanium dioxide; In step S1, the ratio of 2,2'-(2,2,3,3,4,4,5,5,6,6,7,7-dodecafluorooctane-1,8-diyl)bis(ethylene oxide), methacrylic acid and triethylamine is 1 mol: (5-10) mol: (2.1-2.3) mol; In the step S2, the ratio of dodecafluorooctane-1,8-diylbis(methacrylate), terminal hydroxypropyl polysiloxane, isophorone diisocyanate, and dibutyltin dilaurate is 1 mol: (1-1.05) mol: (2-2.2) mol: (0.01-0.03) mol.

2. The method for preparing a water-resistant and anti-aging water-based coating according to claim 1, characterized in that: In the step (1), the ratio of methyl methacrylate, butyl acrylate, acrylic acid, alkenyl organic fluorosilicone polymer and modified titanium dioxide is (20-35) g:100 g:(5-10) g:(2-15) g:(1-10) g.

3. The method for preparing the water-resistant and anti-aging water-based coating according to claim 1, characterized in that: The mass fraction of the ammonium persulfate aqueous solution in step (1) is 5-10wt%.

4. The method for preparing the water-resistant and anti-aging water-based coating according to claim 1, characterized in that: In the step (1), the pH of the ammonia solution is adjusted to 7-8.

5. The method for preparing the water-resistant and anti-aging water-based coating according to claim 1, characterized in that: In step S1, the reaction temperature is 95-110° C. and the reaction time is 2-5 h.

6. The method for preparing the water-resistant and anti-aging water-based coating according to claim 1, characterized in that: In step S2, the reaction temperature is 85-95° C. and the reaction time is 3-8 h.

Citation Information

Patent Citations

  • A water-based acrylic waterproof coating and its preparation method

    CN114456651B

  • High-wear-resistance PCTFE paint for solar cell back plate and preparation method thereof

    CN104403437A

  • Fluorine nanometer composite modified anticorrosion paint

    CN106398499A

  • Water-based fluorosilicone acrylic resin and preparation method thereof

    CN106674442A

  • Water-based fluorosilicone acrylic paint and preparation method thereof

    CN106752606A